TEACHER STRATEGIES IN IMPLEMENTING THE ARABIC CURRICULUM AT PIONEER ELEMENTARY SCHOOL - Fitranur, Rafi; Saharani, Devira; Fakhira, Lu’lu; Maswani (SHAWTUL ARAB, 2025)
This research examines teachers' strategies in implementing the Arabic curriculum at Pioneer Elementary School in Depok, West Java. The background of this study is based on the importance of Arabic language education in Islamic-based schools as well as the need for an effective pedagogical approach, given the “unique” curriculum combined at Pioneer Elementary School, namely: Tahfiz Al-Qur'an, nature concept, and pesantren. The purpose of this study is to identify, describe, and analyse teaching strategies, media, as well as adaptations to student characteristics. The method used was descriptive qualitative through direct observation and in-depth interviews with the head of curriculum and Arabic language teachers. The results of this study show that Pioneer Elementary School implements holistic and innovative strategies, including language days, compulsory Arabic days, language mabit, as well as the use of Interactive media and active conversation methods in the classroom. The school is also adaptive to students with special needs by forming study groups. It is concluded that the success of Arabic learning at Pioneer Primary School comes from the synergy of curriculum, immersive environment, and student-centred pedagogy that can create an inspiring and effective learning experience.